Qânûn Jinâyat Aceh dalam Perspektif Negara Hukum Indonesia - Kamarusdiana Kamarusdiana (AHKAM : Jurnal Ilmu Syariah, 2016)
The Jinâyat Qânûn of Aceh in the Perspective of Indonesian Legal State. Act Number 18 Year 2001 on Specific Autonomy for Aceh as the province of Nanggroe Aceh Darussalam and Act Number 11 Year 2006 on Aceh Government further confirm that the existence of Islamic law in Aceh has become national law, in terms of legal materials, law enforcement officers, as well as increasing public awareness of Islamic law in Aceh. Jinayat Qanun in Aceh province is a renewal of criminal law in Indonesia because a good law must reflect the living law in the society. Therefore, the applied law in Aceh today can be used as a model of the national legal development in Indonesia.DOI: 10.15408/ajis.v16i2.4445